Clinical Sports Medicine - Müller P; 2; 3; Lechner K; 5; Halle M; 6; Braun-Dullaeus R (Dynamic Media Sales Verlag, 2023)
Arterial hypertension is the most important modifiable cardiovascular risk factor for all-cause morbidity and mortality worldwide. It is associated with an increased risk of cardiovascular diseases (CVD) and cognitive impairment. In this regard, accumulating evidence points to beneficial effects of intensified blood pressure lowering by implementation of protective lifestyle patterns (e.g. physical activity, diet) or pharmacotherapy. The aim of this clinical review is to summarize the role of physical activity and/or exercise in prevention and treatment of arterial hypertension.Epidemiology, prospective observational studies, and randomized controlled trials have shown positive effects of physical activity on blood pressure levels in patients with hypertension and in patients with high-normal and normal blood pressure. Thus, physical activity can prevent or slow down micro- and macrovascular end-organ damage.  Physical activity should be recommended for prevention and treatment of all hypertension grades, but most patients with hypertension will concomitantly require drug treatment (depending on hypertension grade and individual cardiovascular risk profile).Currently, increasing attention is directed to the role of personalized exercise prescriptions for prevention and treatment of arterial hypertension and for addressing cardiometabolic risk.Key Words: Exercise, Prevention, Lifestyle, Cardiovascular Risk Factor, Cardiovascular Diseases